Modulation of Hydrophilic/Hydrophobic Character of Porous Environments in Metal-Organic Frameworks via Direct Polymer Capping Probed by NMR Diffusion Measurements - Velasco, Manuel Isaac (2019)
The ability to create extended porous networks, such as those composed of metal-organic frameworks (MOFs), with tailored hydrophilic/hydrophobic character is crucial for adapting such widely used supports to different applications. To achieve this goal, direct polymer inclusion has proven to be a suitable strategy, and functional composite materials with multiple additional properties have been obtained in such a way. We have explored, by means of nuclear magnetic resonance diffusion experiments, the effect of polymer capping using a conducting polymer (polyaminobencylamine - PABA), which results in the positioning of -NH2 moieties on the otherwise eminently hydrophobic surface of Zn-based ZIF-8 MOF nanocrystals. Our results demonstrate that increasingly higher amounts of PABA can confer, aside from conductivity, an increased hydrophilic character to the porous network, while also allowing for the identification of different environments available for water molecule diffusion.